Diversity of endophytic fungi isolated from benzoin-producing tree Styrax sumatrana. Issue 1 (May 2021) - Hidayat, A.; Susilowati, A; Faulina, S A; Elfiati, D; Imanuddin, R; Turjaman, M
Abstract: Styrax sumatrana, native to Sumatra island, Indonesia, is distinctive for its production of benzoin resin. The resin is used for medicinal treatments and commercially valuable. Fungal endophytes are known to produce various bioactive metabolites and may contribute to host resin production or properties. However, the diversity of culturable endophytic fungi associated with S. sumatrana were still underexplored. This study was conducted to examine the distribution and diversity of culturable endophytic fungi associated with tree parts; bark, stem, and leaves of S. sumatrana . A total of 31 endophytic fungi isolates were obtained from S. sumatrana grown in North Sumatera Province, from which 10 genera and 17 species were identified by internal transcribed spacer (ITS) sequence analyses. Among 31 isolates, Fusarium, Phyllostica, Neopestalotiopsis and Pestaliopsis were repeatedly isolated. The species richness S (10), Margalef index D' (3.323), Shannon–Wiener index H' (1.587), and Simpson diversity index Ds (0.756) and low dominant index λ (0.244) of endophytic fungi in the bark of S. sumatrana indicated its high diversity in comparison to other parts of the tree. This finding provides a knowledge of the diversity and organ-type-specificity of endophytic fungal that could be used for biotechnological application in the future.